2009
DOI: 10.1063/1.3198207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Si–N complexes on the electronic properties of GaAsN alloys

Abstract: Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
0
14
2
Order By: Relevance
“…Li et al [23] believed that it is Si Ga -N As that is formed during RTA based on a super cell simulation, while Janotti et al's [24] proposed a (Si-N) As split interstitial model which is more energetically favorable and reasonably accounts for the *0.8 eV photoluminescence (PL) peak observed on the annealed samples. On the other hand, early studies on GaAs:Si have suggested that both V/III ratio and growth temperature will affect Si doping efficiency based on the law of mass action [25]; however, they cannot account for the amount of efficiency decrease observed in our GaNAs samples as well as those in the literature [26,27]. Jin et al [26] also ruled out the possibility by comparing modulation-doped n-AlGaAs/GaAs and n-AlGaAs/GaNAs that the decrease in Si doping efficiency is due to N 2 dimer-related traps.…”
Section: Introductioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Li et al [23] believed that it is Si Ga -N As that is formed during RTA based on a super cell simulation, while Janotti et al's [24] proposed a (Si-N) As split interstitial model which is more energetically favorable and reasonably accounts for the *0.8 eV photoluminescence (PL) peak observed on the annealed samples. On the other hand, early studies on GaAs:Si have suggested that both V/III ratio and growth temperature will affect Si doping efficiency based on the law of mass action [25]; however, they cannot account for the amount of efficiency decrease observed in our GaNAs samples as well as those in the literature [26,27]. Jin et al [26] also ruled out the possibility by comparing modulation-doped n-AlGaAs/GaAs and n-AlGaAs/GaNAs that the decrease in Si doping efficiency is due to N 2 dimer-related traps.…”
Section: Introductioncontrasting
confidence: 63%
“…On the other hand, early studies on GaAs:Si have suggested that both V/III ratio and growth temperature will affect Si doping efficiency based on the law of mass action [25]; however, they cannot account for the amount of efficiency decrease observed in our GaNAs samples as well as those in the literature [26,27]. Jin et al [26] also ruled out the possibility by comparing modulation-doped n-AlGaAs/GaAs and n-AlGaAs/GaNAs that the decrease in Si doping efficiency is due to N 2 dimer-related traps. In this letter, we apply the mutual passivation model to the growth surface and calculated the doping efficiency by Monte Carlo simulation during molecular beam epitaxy (MBE).…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Therefore, bulk diffusion should not be sufficient. However, to explain the extensive passivation in our studies and that of others 33 it was necessary to speculate that surface diffusivity of Si adatoms is higher where ε ο is the permittivity of free space, ε r is the relative static permittivity of GaAs (= 13.1), n ~ (3-10)⋅10 17 /cm…”
Section: Resultsmentioning
confidence: 59%